Expression of Nociceptive Ligands in Canine Osteosarcoma. (8th January 2015) - Shor, S.; Fadl‐Alla, B.A.; Pondenis, H.C.; Zhang, X.; Wycislo, K.L.; Lezmi, S.; Fan, T.M.
<x xml:space="preserve">Abstract</x> Background Canine osteosarcoma (OS) is associated with localized pain as a result of tissue injury from tumor infiltration and peritumoral inflammation. Malignant bone pain is caused by stimulation of peripheral pain receptors, termed nociceptors, which reside in the localized tumor microenvironment, including the periosteal and intramedullary bone cavities. Several nociceptive ligands have been determined to participate directly or indirectly in generating bone pain associated with diverse skeletal abnormalities. Hypothesis Canine OS cells actively produce nociceptive ligands with the capacity to directly or indirectly activate peripheral pain receptors residing in the bone tumor microenvironment. Animals Ten dogs with appendicular OS. Methods Expression of nerve growth factor, endothelin‐1, and microsomal prostaglandin E synthase‐1 was characterized in OS cell lines and naturally occurring OS samples. In 10 dogs with OS, circulating concentrations of nociceptive ligands were quantified and correlated with subjective pain scores and tumor volume in patients treated with standardized palliative therapies. Results Canine OS cells express and secrete nerve growth factor, endothelin‐1, and prostaglandin E2. Naturally occurring OS samples uniformly express nociceptive ligands. In a subset of OS‐bearing dogs, circulating nociceptive ligand concentrations were detectable but failed to correlate with pain status. Localized foci of nerve terminal proliferation were identified in a minority of primary bone tumor samples. Conclusions and Clinical Importance Canine OS cells express nociceptive ligands, potentially permitting active participation of OS cells in the generation of malignant bone pain. Specific inhibitors of nociceptive ligand signaling pathways might improve pain control in dogs with OS.